1993
DOI: 10.1021/j100115a011
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of dimeric cis-9-octadecenoic acid in its pure liquid state as observed by near-infrared spectroscopic measurement

Abstract: The dissociation of dimers of cis-9-octadecenoic acid into its monomeric species in its pure liquid was studied by near-infrared spectroscopic measurements over a temperature range of 8.6-84.4 OC. An absorption band at 1445 nm, which is attributed to the free OH of the fatty acid molecules, appeared even at relatively low temperatures; its peak height increased with increasing temperature. This shows that the dissociation of the acid dimers occurs even at low temperatures and increases with increasing temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 1 publication
1
58
1
Order By: Relevance
“…5,6 The dissociation of dimers of cis-9octadecenoic acid into monomeric species in its pure liquid form was investigated; the study showed that the dissociation occurs even at low temperatures and increases with increasing temperature. The molar absorption coefficient and the absorbance for the neat sample at various temperatures, T, produce the temperature dependence of the degree of dissociation, α, for dimeric cis-9-octadecenoic acid into monomers in the liquid state.…”
Section: Structure and Self-association Of Fatty Acids And Alcoholsmentioning
confidence: 99%
“…5,6 The dissociation of dimers of cis-9octadecenoic acid into monomeric species in its pure liquid form was investigated; the study showed that the dissociation occurs even at low temperatures and increases with increasing temperature. The molar absorption coefficient and the absorbance for the neat sample at various temperatures, T, produce the temperature dependence of the degree of dissociation, α, for dimeric cis-9-octadecenoic acid into monomers in the liquid state.…”
Section: Structure and Self-association Of Fatty Acids And Alcoholsmentioning
confidence: 99%
“…12 The results with 5676 and 5790 cm -1 follow this structural change in the temperature range. For example, xc values estimated with 5676 and 5790 cm -1 agree with the structural changes of OA in both cases of LMedS and LS estimator.…”
Section: Curve Fitting With Simulated Data Setmentioning
confidence: 70%
“…polymers. [33][34][35][36][37][38][39][40][41][42][43] The reason why NIR spectroscopy is very useful for the studies of self-associated molecules is that the absorption bands in the NIR region (14,000-4000 cm -1 ) are mainly due to overtones and combinations associated with the groups having a hydrogen atom such as C-H, O-H and N-H. Anharmonicity of X-H bonds is very large and the fundamental modes of X-H stretching appear in the high frequency region of the IR spectra. Therefore, a NIR spectrum is, in general, very complicated but in some sense it enhances bands due to X-H groups.…”
Section: Two-dimensional Nir Correlation Spectroscopy Studies Of Tempmentioning
confidence: 99%